(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The peculiarities of the heteroligand complexes (HLC) formation of Ni (II), Co (II) and Mo (VI) on silica gel with chemically bounded aminopropyl (C-NH2) and ethylenediamine groups (C-en), and silica gel with impregnated polyhexamethyleneguanidine chloride (C-PHMG) with unitiol and Pyrocatechol Violet were studied. According to the data of DRS analysis composition of the complexes were found, and by comparing of the diffuse reflecta spectra of adsorbates with electronic absorption spectra of complexes with these reagents in solution it was shown that the heteroligand complexes on the surface are similar to the complexes in solution. The stability of heteroligand complexes depends on the method of synthesis was studied. The possibility of using of the obtained colored HLC to test-, sorption-spectrometric and colorimetry methods of analysis was shown.